Exploring Green Factors and Green Practices: A Case Study of Thailand’s Best Green Small Hotel - Chiangphan, Narinsiree; Vongsaroj, Rugphong (Journal of Multidisciplinary in Social Sciences, 2024)
This qualitative study aimed to investigate the components of Green Practices and Green Factors that contribute to the successful implementation of sustainable practices in small hotels in Thailand. The study utilized a framework derived from world-class green hotels and incorporated the Triple Bottom Line (TBL) concept. Through interviews with 12 small hotel owners and managers in the Thailand Active Beach Cluster, an outline for implementing Green Practices was developed. Content analysis allowed for a thorough and structured analysis of the interview data, enabling the identification of key insights and trends that informed the development of the Green Practices implementation plan. The findings revealed that small hotel Green Practices comprised four dimensions: optimizing the utilization of community resources (OCR), integrating environmental concepts to gain competitive advantage (ICA), Developing and disseminating environmental awareness to customers (DEC), and protecting the environment (PE). Additionally, through a comprehensive examination of literature and interviews, 20 Green Factors were identified as crucial elements contributing to the successful implementation of Green Practices in small hotels in Thailand: Strategic planning, Innovative and energy-efficient technologies, Perceived Green standard and green law, Competitors, Supplier, Government campaign, Effective marketing, Owner’s awareness, Partner, Environmental leadership, Green knowledge, Hotel guests’ awareness, Cost allocation for environment activities, Infrastructure and system investment, Trend, Government regulations, Employee adaptability, Rewards and incentive, Facilities and Resources, and Clear Organizational identity. These findings offer valuable insights into the effective and efficient implementation of Green Practices in the context of small hotels in Thailand. This study can serve as a valuable reference point for various types of hotels worldwide, facilitating the adoption of green practices that benefit not only the environment but also the long-term economic prospects and reputation of the hospitality sector as a whole.